Empreendedor social: um estudo de caso - Lima, Cássia Maria Paula (2013)
The purpose of this dissertation is to understand the social entrepreneur, from the observation his practice and seeking to consolidate a comprehensive overview, an understanding of this agent that incorporates the approaches of different disciplines that study. The social entrepreneur presents features, depending on who defines it: Administrators, psychologists, sociologists and economists. It is relevant to add that notice of any fact or social action is not a simple task, as society is, by its very nature and in any instance, complex; the complexity grows in the area of current humanitarian aid because of the multiple actions arising in this new segment, such as: Investment Fund in order to generate social impact, social business, social transparency, governance, 2.5 and municipal councils with the new social movements. As well as new actors appear institutions: social entrepreneurs and investors, that coexist with other well-known actors in society, as philanthropists. To this end, it was promoted a qualitative case study of a social entrepreneur from her speech and another six people that were indicated by her and who participated in the help project to others. Xinha from Liga Solidária (Non Governamental Organization) was considered from the main guidelines of the Grounded Theory, which is a methodology that sets out the research process as non-linear. The main conclusion is this social entrepreneur acts in networks to achieve improvements to a community. It was taken into account the studies on Granovetter's weak ties on networks and embeddedness to conclude that she actively worked to build a proactive development of the network, understanding local issues, recovering lost links, and sharing knowledge. Were thus highlighted the features that sets her apart as a social entrepreneur, who is the focus on social work and the promotion of innovation in society. What remained was the path taken by Xinha corresponded to her own process of training as a social entrepreneur